A Potential Friends Recommendation Model for Location-Based Social Network - Xiaochen Sun; Yabin Xu (Dianxin kexue)
To make service convenient and improve user experience degrees, recommendation service has become more and more important to users in the location-based social network（LBSN）. An improved potential friends recommendation in LBSN, which is based on the relationship among friends and the similarity of locations, was proposed. First of all, the user interest pointsin each position weight with friends' relationship, check-in feature and historical recordwere calculated. Then position weight and the friend relationship were used to calculate the friends' similarity and location similarity. Finally, potential friends to user based on the friends' similarity and location similarity were recommended. The experimental results show that the proposed model is effective.